Totally Implantable Venous Access Devices: A Randomized Controlled Trial on the Effect of Psychological Support on Quality of Life and Body Image (BI-PORT) - Pinto, Eleonora; Granziera, Elisa; Cagol, Matteo; Cappellato, Sandra; Alfieri, Rita; Mari, Valentina; Meroni, Muzio; Zagonel, Vittorina; Conte, Pierfranco; Pilati, Pierluigi; Castoro, Carlo; Cavallin, Francesco; et al. (Frontiers in Psychology, 2021)
Background The presence of a totally implantable venous access devices (TIVAD), as any permanent or semi-permanent medical device, have an impact upon patient quality of life. Therefore, the purpose of this trial was to evaluate the efficacy of a psychological support for patients undergoing this procedure. Methods This randomized control trial (RCT) aimed to compare the efficacy of a psychological intervention vs. standard care on quality of life in patients receiving TIVAD for chemotherapy treatment (ClinicalTrials.gov NCT02075580). The trial was conducted at the Veneto Institute of Oncology IOV-IRCCS (Padua, Italy) between October 2013 and September 2018. Participants were neoplastic adults receiving TIVAD for chemotherapy treatment for any cancer, not undergoing visible demolitive interventions, without psychopathological diagnosis and language understanding. Exclusion criteria were patients without a diagnosis of cancer, or with psychopathological diagnosis, or with language misunderstanding. Results The variation of C30-QL2 and of BR32-BI was not statistically different between intervention and control arms in males and in females. However, the variation of C30-SF was statistically better in intervention than control arm in males (MD 22.3, 95% CI 3.5 to 41.0) but not in females (MD -2.7, 95% CI -24.0 to 18.7). The variations of the other secondary outcome measures were not statistically different between intervention and control arms. Discussion In conclusion, psychological support did not show any clear advantages on global quality of life and body image perception in patients at 15 days after TIVAD insertion for chemotherapy. On the other hand, male patients might benefit from even a very short psychological counseling before or during chemotherapy even if they do not seem to ask for it.